THE INFLUENCE OF LOCAL LANGUAGE ON THE USE OF INDONESIAN LANGUAGE IN THE LEARNING CLASS - Anita Candra Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Regional languages are one of the characteristics that are owned by Indonesia and their existence is still very well preserved in Indonesia, but the use of regional languages cannot be used in any place, for example in certain institutions and when formal associations are held. Why should this be applied because Indonesia has one unit that forms the basis of Indonesian unity, namely the official Indonesian language, if the use of regional languages is used in any place the impact can cause misunderstandings that will lead to divisions between people. The impact of the use of regional languages that are not used in other places, namely in educational institutions where the use of regional languages should not be used during the learning process except in certain learning because it will interfere with the process of understanding the material to students. Why is that because Indonesia has many tribes, cultures, languages, religions and races whose unity must be maintained. In this discussion, it will be explained how the influence of regional languages on classroom learning will be explained.